EARCT- ENVIRONMENT FOR AUTOMATED RANK BASED CONTINUOUS AGENT TESTING - Kumar, Ashok; Goyal, Vinay (International Journal of Computing, 2014)
Testing MAS (Multi-agent System) is a challenging task because these systems are distributed, complex and autonomous in nature. Agents exist in an open environment having their own locus of control and they require context awareness. So due to these agent’s characteristics, testing MAS system using existing testing techniques becomes a very tedious job. Agents also pose problems regarding message communication and semantic interoperability, as well as synchronization with other agents existing in the environment. All these features are known to be hard not only to design and to code, but also to test. In this paper we will propose a unique environment EARCT to test MAS keeping in mind the essential software engineering paradigms such as effort consumed, errors revealed etc.